Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1111/j.1464-410x.1993.tb16257.x
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic and Clinical Aspects of Ileal Low Pressure Bladder Substitutes

Abstract: Twenty-three patients with an ileal bladder substitute formed after cystectomy for invasive bladder cancer were evaluated clinically and urodynamically between 3 and 38 months post-operatively. The urodynamic measurements were compared with the clinical findings. After re-education of the patients' voiding habits the mean voiding volumes of the bladder substitutes stabilised 6-9 months post-operatively at 350 ml. The frequency of micturition was 3 to 5 times during the day and once or twice at night. The maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…On the other hand, a reservoir made from 10 cm less of bowel, i.e., from 30 cm instead of 40 cm (left) would be too small and the pressure too high if it were filled to capacity, particularly at night namically proven low-basal-pressure characteristics (Fig. 7a) [5,8] as well as nerve-sparing dissection of the prostate [42] and cystectomy with preservation of the pelvic plexus and its autonomic fibers to the membranous urethra [6,13] and an attempt to preserve a maximally possible length of membranous urethra, urinary continence is not perfect in all patients. In contrast to patients treated by radical prostatectomy, patients with an orthotopic intestinal bladder substitute have no detrusorsphincteric reflex, which increases the closing pressure in the membranous urethra in response to rising intravesical pressure [30].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, a reservoir made from 10 cm less of bowel, i.e., from 30 cm instead of 40 cm (left) would be too small and the pressure too high if it were filled to capacity, particularly at night namically proven low-basal-pressure characteristics (Fig. 7a) [5,8] as well as nerve-sparing dissection of the prostate [42] and cystectomy with preservation of the pelvic plexus and its autonomic fibers to the membranous urethra [6,13] and an attempt to preserve a maximally possible length of membranous urethra, urinary continence is not perfect in all patients. In contrast to patients treated by radical prostatectomy, patients with an orthotopic intestinal bladder substitute have no detrusorsphincteric reflex, which increases the closing pressure in the membranous urethra in response to rising intravesical pressure [30].…”
Section: Discussionmentioning
confidence: 98%
“…The urethral catheter is left on free drainage for 2 more days before it is removed; further details have been reported elsewhere [35,36]. After catheter removal, the patients were instructed to void every 2 h, first in a sitting position, by relaxing the pelvic floor, and, if necessary, by abdominal straining [5]. The patients were encouraged to drink 2-3 1 of fluid per day and to ensure sufficient salt intake to avoid a salt-loss syndrome due to hypoosmolar urine in the ileal bladder substitute and to reduce the risk of acidosis from hypovolemia [20].…”
Section: Surgical Techniquementioning
confidence: 99%
“…That is a daytime frequency of 3-5 times with satisfactory con tinence and a mean voiding volume around 350 ml. Dur ing sleep, patients should have to awake to void once or twice [4], To overcome the deficits, Camcv modified his tech nique by the use of a detubularized ileal segment [2], The nighttime continence rate improved to 78% and 96% of the patients could stay dry in the daytime. Most patients achieved continence within 3-4 months following the operation [1,2], There are several methods of construction of the reser voir after detubularization of the ileum [ 1,[4][5][6]; however, there is no significant difference in the surgical morbidity, continence rate and urodynamic results among all these methods [1,2,[4][5][6][7], The patient's compliance and willing ness to become actively involved in the postoperative re education and training courses are even more important.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients achieved continence within 3-4 months following the operation [1,2], There are several methods of construction of the reser voir after detubularization of the ileum [ 1,[4][5][6]; however, there is no significant difference in the surgical morbidity, continence rate and urodynamic results among all these methods [1,2,[4][5][6][7], The patient's compliance and willing ness to become actively involved in the postoperative re education and training courses are even more important. A well-trained patient may void quite well in spite of a poor urodynamic result [4,7], In our study, the daytime continence rate (93%) is compatible with the data reported previously (table 3). The mean interv al from surgery to achievement of com plete daytime continence was 3 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation